The Influence of Customer Value and Customer Experience on Customer Loyalty at Soya Drink Ciamis - Maulana Hasan, Ariandi; Darna, Nana; Yulia, Lia (Journal of Economics Review (JOER), 2025)
Purpose: This study aims to examine the influence of Customer Value and Customer Experience on Customer Loyalty among consumers of Soya Drink Ciamis. The research focuses on understanding how perceived value and experiential factors contribute individually and jointly to fostering long-term customer commitment toward a local beverage brand. Research Method: The study adopts a descriptive quantitative approach with an incidental sampling method, involving 94 respondents selected from a population of 1,498 customers. Data were analyzed using descriptive statistics, simple and multiple correlations, multiple linear regression, coefficient of determination, and hypothesis testing through t-tests and F-tests. Results and Discussion: The results reveal that both Customer Value and Customer Experience have a positive and significant impact on Customer Loyalty. Emotional and price value dimensions were rated as the highest in terms of customer value, while sensory and relational aspects dominated the overall customer experience. Although overall loyalty was intense, improvements are needed in habitual consumption and emotional attachment. The simultaneous effect of both variables shows a more substantial influence, confirming their synergistic role in shaping loyalty behavior. Implications: The study highlights that enhancing perceived customer value and optimizing customer experience are key strategies for strengthening loyalty. Managers should focus on emotional, social, and performance-based factors to build sustainable customer relationships.